OTOMATISASI TUKAR FAKTUR YANG TERINTEGRASI (STUDI KASUS PADA RSIJCP) - Ruwaidah, Ida; Ahmad, Topik B.; Sugiarto, Jepi; Aryani, Neni Dwi (Taksasila Edukasi Insani, 2024)
This study discusses the analysis of changes in the manual invoice exchange process flow to an integrated invoice exchange system that has an impact on the automation of financial processes at RSIJCP. In an increasingly complex and competitive business environment, RSIJCP needs a system that can manage and process invoices quickly and without errors. An integrated invoice exchange system allows companies to automate many manual processes, such as matching invoices with purchase orders, verifying data, and tracking payment status. The implementation of this system can also reduce the risk of human error and fraud, resulting in more transparent and reliable operations. This study describes the current process flow and the proposed process flow, with a descriptive qualitative methodology through observations and interviews involving financial officers. Furthermore, this study highlights the importance of further analysis in order to create a more effective and efficient work process. The expected result of this process change is to create a more effective and efficient work process so that automation is created in the financial process. So that the Invoice Exchange System integrated with the Financial System can reduce the workload and risks that occur in the Invoice Exchange process carried out manually. Keywords : Automation, Invoice Exchange, E-Invoicing